Balloon Eustachian tuboplasty treatment of longstanding Eustachian tube dysfunction. Issue 7 (15th May 2017) - Singh, T; Taneja, V; Kulendra, K; Farr, M; Robinson, J; Rejali, D
Abstract: Background: Eustachian tube dysfunction is a poorly defined condition associated with various symptoms and it can predispose to middle-ear disease. Balloon dilation Eustachian tuboplasty has been proposed as a treatment for Eustachian tube dysfunction. Objective: To evaluate the subjective and objective outcomes of balloon dilation Eustachian tuboplasty in patients with recurrent, previously treated chronic Eustachian tube dysfunction. Methods: The study was conducted on 11 patients (13 ears) who had undergone previous unsuccessful medical and surgical treatment. Tympanometry was the primary outcome measure. Secondary outcome measures included pure tone audiogram assessment and seven-item Eustachian Tube Dysfunction Questionnaire score. Results: Balloon dilation Eustachian tuboplasty resulted in significant improvements in 11 patients' subjective but not objective outcome measures. Conclusion: The objective abnormality and subjective symptoms in Eustachian tube dysfunction may represent two distinct pathological processes, which may nevertheless influence and exacerbate each other.